Behaviour of sea sand recycled concrete filled steel tube under axial compression. Issue 4 (17th May 2019) - Huang, Yijie; Wu, Jida; Wang, Qing
Abstract : This paper presents the results of an experimental study of sea sand recycled concrete filled circular steel tubes (SSRCFSs) under axial compression. The mechanical behaviours of axially loaded SSRCFSs were investigated. Two different parameters were considered: sea sand chloride ion (Cl − ) content and recycled coarse aggregate (RCA) replacement percentage. Typical influences of sea sand Cl − and RCA contents on the bearing capacity, deformation and load–deformation curve of SSRCFS were studied. The test results showed that the typical failure mode of the SSRCFSs was similar to that of ordinary concrete filled steel tubes. The axial load–deformation curves of the SSRCFSs could be divided into elastic, plastic growth, declining and steady stages. It was found that the bearing capacity of SSRCFSs increased with decreasing RCA replacement percentage. The effect of sea sand Cl − content on the mechanical behaviour of the SSRCFSs decreased with an increase in RCA replacement percentage. The peak strain of the specimen could be enhanced due to the low modulus of the RCA, but this improvement decreased with increasing sea sand Cl − content. Finally, numerical expressions were developed to obtain the peak load and load–deformation curve of the SSRCFSs. The calculated results were in line with the experimental data.